c - (3YQaGf(B, (3eMeO (BIrfan, Muhammads (Calcutta : [Calcutta School-Book Society], 1933)
The Arabic Reader, or, select extracts from various Arabic writers.
Reproduction of the original from The British Library.
Keywords: Arabic language -- Readers